Understanding the Crime of Money Laundering in the Concept of Criminal Law in Indonesia - Muhammad Ridwan Lubis; Cut Nurita (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Nowadays, the patterns and behaviors of Money Laundering constitute efforts to conceal or disguise the origin of money or wealth resulting from criminal activities through various financial transactions, making the money or wealth appear as if it comes from legal activities. Several common or frequent actions are taken in the process of committing money laundering to "cleanse" the proceeds of crime. Firstly, the money generated from criminal activities is transformed into a form that arouses little or no suspicion through placement into the financial system using various methods. The second step involves engaging in complex, layered, and anonymous financial transactions with the aim of separating the proceeds of crime from their source into various accounts, making it difficult to trace the origin of the funds, essentially hiding or disguising the origin of the wealth resulting from criminal activities (layering). The final step is where the perpetrator reintroduces the funds that have been obscured in their origin into legitimate wealth, whether to be enjoyed directly, invested in various forms of material or financial wealth, used to finance legitimate business activities, or to fund further criminal activities (integration).